Studi Adsorpsi Furfural Menggunakan Karbon Aktif dari Kulit Durian Termodifikasi - Sitinjak, Philip Dohan Rea; Husin, Amir (Talenta Publisher (Universitas Sumatera Utara), 2021)
Furfural is an aromatic aldehyde, classified as hazardous material that cause environmental impact, especially harmful for humans if consumed. Furfural removal in water is necessary to overcome the negative impact. Furfural removal can be carried out using adsorption of activated carbon from durian shell. This study determines contact time and reaction kinetic using modified activated carbon which carried out in 7 stages: preparation of furfural main solution 1000 ppm, furfural work solution, determining furfural standard curve, adsorption time, best mass and adsorption capacity of activated carbon, isotherm adsorption and kinetics. The parameters measured are contact time, capacity, furfural adsorption kinetics. Filtrate testing is carried out using UV-Spectrophotometry. Results that obtained in this study are best contact time at 75 minutes with reaction order; reaction contant (k); linear regression (R2) are 1.5; 3.966 Ã— 10-5 (mg/g)/s; 0.9451 respectively. The isotherm adsorption model is Langmuir Isotherm. Â